2018
DOI: 10.1007/s11469-018-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Sharing, Group-Buying, Social Supply, Offline and Online Dealers: how Users in a Sample from Six European Countries Procure New Psychoactive Substances (NPS)

Abstract: Given the multiple ways of regulations and market situations for new psychoactive substances (NPS), it is of interest how NPS users procure their drugs in different countries as well as in different user groups. Data comes from a face-to-face and online survey conducted in six EU countries, covering three groups of current (12-month) adult NPS users: (1) socially marginalized, (2) users in night life, and (3) users in online communities. While the supply situation differed considerably between countries, frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Users have now switched to other sources. A survey of 663 NPS users showed that since the NpSG’s introduction, only 6% purchased NPS from headshops, whereas 61% obtained NPS through the internet [58]. The IFT evaluation found that while street dealers were a minor source of NPS in 2016, accounting for 15% of sales, by 2017 they had become the main source of NPS with 56% of sales, which rose to 72% in 2019 [55].…”
Section: Evaluation 2: the German Npsgmentioning
confidence: 99%
“…Users have now switched to other sources. A survey of 663 NPS users showed that since the NpSG’s introduction, only 6% purchased NPS from headshops, whereas 61% obtained NPS through the internet [58]. The IFT evaluation found that while street dealers were a minor source of NPS in 2016, accounting for 15% of sales, by 2017 they had become the main source of NPS with 56% of sales, which rose to 72% in 2019 [55].…”
Section: Evaluation 2: the German Npsgmentioning
confidence: 99%
“…Eine weitere nationale Besonderheit zeigt sich in der polnischen Stichprobe, für die als einzige sowohl marginalisierte als auch internetaffine und Nachtleben-orientierte aktuelle NPS-User in nennenswertem Maße rekrutiert werden konnten. Dies dürfte wiederum -trotz weitgehendem Verbot -der speziellen NPS-Geschich- [18,21].…”
Section: Diskussionunclassified
“…Um Näheres über die Konsumsituation herauszufinden, ist es sinnvoll, sich direkt an NPS-Erfahrene mit Bezug zu ihrer Lebenswelt zu wenden, wie es in Deutschland zuvor bereits im Rahmen zweier Online-Befragungen erfolgte [15,16]. Die im Folgenden präsentierten Ergebnisse entstammen dem EU-Projekt "NPS transnational" [17][18][19][20][21][22]. Arbeitsziele waren die Bestimmung von Art und Ausmaß des Gebrauchs von NPS in unterschiedlichen Gruppen von Konsumierenden (inklusive Erkenntnisse über Konsummotive, Risiken und Erwerbswege) in sechs EU-Ländern.…”
Section: Introductionunclassified
“…The cause is the development of information and communication technology. Trading is often carried out manually (offline) [2], with bartering [3] and faceto-face [4]. People come to a shop or company to make transactions in person (face to face).…”
Section: Introductionmentioning
confidence: 99%